Sedimentation Analysis in the Cihaur Irrigation Channel, Cilacap Regency, Central Java - Fauzan, Rifqi; Rifki , Dega Muchamad; Abdurohman, Salim; Edhy P, Sulistijo (Ridwan Institute, 2025)
This thesis analyzes sedimentation in the Cihaur irrigation canal within the Manganti Irrigation Area (D.I. Manganti), Cilacap Regency, which irrigates 700 hectares of agricultural land from an irrigation system covering a total of 26,153 hectares. The study examines the impact of sedimentation on the capacity and efficiency of the 22.62 km long irrigation canal. The analysis of sedimentation-causing factors is based on Sasrodarsono’s theory (1989), which includes the area of erosion, geological and topographical conditions, meteorological factors (particularly high rainfall intensity), hydraulic characteristics (a flow rate of 136.524 m³/second), vegetation, and human activities within the Citanduy River Basin (DAS Citanduy). The impacts of sedimentation include a reduction in canal capacity, decreased hydraulic efficiency, and increased maintenance costs. The research method uses a descriptive analytical quantitative approach, includingmeasurements of discharge, sedimentation volume (20.405 m³/second), granulometric analysis (dominated by fine sand and silt with a silt content of 58%), and water content (86% for settled sediment, 292% for floating sediment). Correlation analysis indicates a relationship between high rainfall and increased sedimentation. The results show that sedimentation significantly reduces irrigation capacity and efficiency. For example, the flow in the Simpellu I primary canal decreased from 136.524 m³/second to 116.119 m³/second due to sedimentation amounting to 20.405 m³. Recommended solutions include sediment dredging, canal normalization, upstream erosion control (reforestation, terracing, mulching), the construction of sediment control structures (sediment traps, settling basins, check dams), proper canal design, regular cleaning and maintenance, and active participation from farmers. The study is limited by a lack of historical data and the narrow scope focused solely on the Cihaur irrigation canal. Irrigation Efficiency For example, the discharge in the Simpellu I primary canal decreased from 136.524 m³/second to 116.119 m³/second due to sedimentation of 20.405 m³. Recommended solutions include sediment dredging, canal normalization, erosion control upstream (reforestation, terracing, mulching), construction of sediment control structures (sediment traps, settling ponds, check dams), appropriate canal design, routine cleaning and maintenance, and active farmer participation. This research has limitations regarding historical data and the study’s scope, which is limited to the Cihaur irrigation canal.